Enhancing Candida auris diagnosis: a comprehensive evaluation of VIASURE Candida auris real-time PCR detection kit for rapid diagnostic responses - Blanca Dehesa-García; Henar Alonso; María Paz Peris; Blanca Fortuño; Pilar Abad; Antonio Rezusta; Ana Milagro (Microbiology Spectrum)
ABSTRACT Candida auris, a yeast that is highly resistant to antifungal treatments, represents a significant healthcare concern due to its rapid spread through surface contamination and patient colonization. A recent outbreak at the Miguel Servet University Hospital in Zaragoza, Spain, highlighted the urgent need for rapid diagnostic responses. The current 4-day duration for microbiological culture results hinders timely patient isolation and transmission prevention. This study aims to evaluate the VIASURE Candida auris Real-Time PCR Detection Kit (Certest Biotec) for diagnostic performance and analytical specificity compared to the standard methodology based on culture and MALDI-TOF MS characterization. From August 2023 to December 2023, the Microbiology Service of the Miguel Servet University Hospital processed 816 diagnostic samples. Accuracy testing resulted in adequate clinical validation values, as presented here: sensitivity, 0.98 (95% confidence interval [CI], 0.90 to 1); specificity, 1 (95% CI, 0.99 to 1); positive predictive value, 0.98 (95% CI, 0.90 to 1); and negative predictive value, 1 (95% CI, 0.99 to 1). The implementation of this molecular biology test in the laboratory promises to improve diagnostic efficiency by allowing rapid patient isolation, initiation of appropriate treatment, and effective isolation measures.IMPORTANCECandida auris, a resilient and antifungal-resistant yeast, poses a significant healthcare threat due to its rapid spread. A recent outbreak at a hospital in Zaragoza, Spain, emphasized the urgent need for faster diagnostics. The current four-day wait for culture results hampers timely patient isolation. This retrospective and comparative study demonstrates the favorable clinical parameters of a commercially available molecular diagnostic kit. The kit allows enhanced diagnostic efficiency, swifter patient isolation, and more effective control measures in the laboratory. In conclusion, the kit addresses the pressing challenges presented by C. auris in healthcare.